National pharmacovigilance system and current practice in the Turkish Republic of Northern Cyprus [Kuzey Kıbrıs Türk Cumhuriyeti'nde ulusal farmakovijilans sistemi ve mevcut uygulamalar] - (:unkn) unknown (Marmara University, 2012)
During drug development drug safety is assessed in detail, but these preclinical researches do not provide the whole data of safety. Therefore, drugs should be monitored in the market and care must be given to their adverse effects. Many countries founded their own national pharmacovigilance systems. In developing countries, because of the delays in the foundation of pharmacovigilance systems and inability to access existing data for conducting pharmacoepidemologic studies, the data belonging to developed countries are used. When cultural, genetic factors and many other local factors were taken in consideration, this may not be relevant. In Turkish Republic of Northern Cyprus (TRNC) all drug retractions till now were done according to outsourcing data because of the lack of national data. TRNC Ministry of Health and Near East University Faculty of Pharmacy have signed the founding protocol of National Pharmacovigilance Center in 2008. As pharmacovigilance system works successfully and achieves its goals, this will contribute patient safety, moreover reduce health expenditures.
Keywords: Adverse drug reaction; Pharmacovigilance; Pharmacovigilance center; Reporting; Turkish Republic of Northern Cyprus